THE FUNCTION OF THE DPRD'S RIGHT OF INTERPLATION IN SUPERVISION OF REGIONAL HEAD POLICIES - Ade Hilmy Raihan; Mukhlis Mukhlis (Inspiring Law Journal, 2025)
The Regional People's Representative Council (DPRD) has an equal position and works closely with the government. Therefore, the Regional Representative Council is required to incorporate community aspirations into regional policies and carry out its oversight function. Duties of the Regional People's Representative Council (DPRD). Taking into account the duties and authorities of the Regional People's Representative Council (DPRD), this will result in an increase in the role and function of the regional legislative body or the Regional People's Representative Council (DPRD) in terms of legislation, oversight, and budgetary functions. In addition, Law of the Republic of Indonesia Number 13 of 2019 concerning the Third Amendment to Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council will also enhance these roles and functions. One of the important duties of the Regional People's Representative Council (DPRD) is to carry out its oversight function.The research takes up the problem of the implementation of the DPRD's right of interpellation function in supervising regional head policies. Obstructing the implementation of the DPRD's right of interpellation in supervising regional head policies. The legal consequences of the DPRD's right of interpellation in supervising regional head policies.Results and Discussion of the Implementation of the DPRD's Interpellation Rights Function on the Supervision of Regional Head Policies, namely the DPRD and the regional head have a supervisory relationship, both as members and as institutions. Obstacles to the Implementation of the DPRD's Interpellation Rights on the Supervision of Regional Head Policies, namely One of the obstacles that often occurs in the implementation of the DPRD's interpellation rights is differences of opinion between members and factions. The DPRD's interpellation rights can be proposed if they receive approval from a DPRD plenary session attended by more than half of the DPRD members. The DPRD's interpellation rights can be hampered if the proposal submitted does not receive approval from the DPRD plenary session. The legal consequences of the DPRD's interpellation rights on the supervision of regional head policies, namely the Legal consequences of the Implementation of the DPRD's interpellation rights against the Regional Government can give rise to various significant legal consequences. Legal consequences refer to the consequences or results that arise as a result of an action, decision, or event that is regulated or influenced by law.